Correction to: Is diet partly responsible for differences in COVID‐19 death rates between and within countries?. Issue 1 (26th October 2020) - Bousquet, Jean; Anto, Josep M.; Iaccarino, Guido; Czarlewski, Wienczyslawa; Haahtela, Tari; Anto, Aram; Akdis, Cezmi A.; Blain, Hubert; Walter Canonica, G.; Cardona, Victoria; Cruz, Alvaro A.; Illario, Maddalena; et al.
Abstract : An amendment to this paper has been published and can be accessed via the original article.